SEALING STRUCTURE RESEARCH ON RUBBER OF THE COMPRESSION OPEN HOLE PACKER - LI Bin; ZHANG DongYang; LI Qiang; SHEN HuanYu; YANG Shuang (Jixie qiangdu)
The compression open hole packer was one of the core parts of horizontal well open hole staged fracturing completion technology. Due to working in an environment of high temperature,high pressure and complex and deep stratum,the packer setting often turned to low pressure and losed efficacy earlier. The main reason was that the sealing structures of the packer were unreasonable,which reducing the contact stress between rubber and well wall. Based on the elasticity theory,the maximum contact pressure of packer rubber setting was derived and a new sealing structure of compression open hole packer was constructed which consisted of four-rubbers. By using ABAQUS,the contact stress distribution between conventional and new combined rubbers were comparativelly analyzed in the same condition,and the head face bevel of new type combined rubbers was optimized.In the end,the effects on contact stress of new type combined rubber tube caused by friction factor were discussed. The analytical result shows that the new sealing structure could transfer the setting force to sealing rubbers more effectively,and the contact stress significantly increased and distributed more evenly,which ensuring the reliability of the sealing rubber.